2013
DOI: 10.1186/1546-0096-11-21
|View full text |Cite
|
Sign up to set email alerts
|

Pain experience in children with juvenile idiopathic arthritis treated with anti-TNF agents compared to non-biologic standard treatment

Abstract: BackgroundAnti-TNF agents have proven efficacy in children with severe juvenile idiopathic arthritis (JIA) who are unresponsive to standard therapy. Therefore pain reduction or elimination could be expected. The aim of this study was to compare the pain experience in children with JIA treated with anti-TNF agents (n = 41) or non-biologic standard treatment (n = 50).MethodsAll children completed a 2-week pain diary and, for children treated with anti-TNF agents, measures of pain-coping and pain-specific beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 52 publications
(64 reference statements)
4
49
0
Order By: Relevance
“…Data represent mean ± SEM. *P < 0.05, **P < 0.01, # P < 0.001. ment (63,64). Preclinical studies should be performed to further examine these possibilities.…”
Section: Figurementioning
confidence: 99%
“…Data represent mean ± SEM. *P < 0.05, **P < 0.01, # P < 0.001. ment (63,64). Preclinical studies should be performed to further examine these possibilities.…”
Section: Figurementioning
confidence: 99%
“…Activated glial cells in the dorsal horn of the spinal cord and infiltrating macrophages or activated satellite glial cells in the DRGs produce proinflammatory cytokines that sensitize the sensory system (Ren and Dubner, 2010). Therefore, these neuroinflammatory pathways, including spinal cord and DRG cytokine production and glial cell activation, represent potential therapeutic targets for treating persistent pain states (Ren and Dubner, 2010;Graeber and Christie, 2012;Ji et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain is a major complaint of many patients suffering from chronic inflammatory diseases, including rheumatoid arthritis and inflammatory bowel disease. In these conditions, pain may even persist after successful treatment of the inflammation (Bielefeldt et al, 2009;Lee et al, 2011;Lomholt et al, 2013). Current treatments provide modest pain relief at best, due to lack of effectiveness or because treatment has to be suspended due to severe side effects (Borsook et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism behind the alteration from acute inflammatory pain to chronic noninflammatory pain is not fully understood, though animal models have shown TNF-α to play a role in the sensitization of the central nervous system [33,34]. Studies evaluating the effect of anti-TNF-α treatment on pain in humans have reported divergent results [29,35]. The incidence rate of developing chronic non-inflammatory pain is reported to be highest the first 12 months after diagnosis of RA [36], also described in acute back pain [37,38].…”
Section: Das28 Over 5 Years Esr Over Timementioning
confidence: 99%